Responses of photosynthesis and component processes to drought and temperature stress: are Mediterranean trees fit for climate change?. (16th September 2019) - Sperlich, D; Chang, C T; Peñuelas, J; Sabaté, S
Abstract: Global warming is raising concerns about the acclimatory capacity of trees and forests, especially in Mediterranean-type ecosystems. The sensitivity of photosynthesis to temperature is a key uncertainty for projecting the magnitude of terrestrial feedbacks on future climate change. While boreal, temperate and tropical species have been comparatively well investigated, our study provides the first comprehensive overview of the seasonal acclimatory responses of photosynthesis and its component processes to temperature in four Mediterranean climax species under natural conditions. We quantified seasonal changes in the responses of net photosynthesis ( A net ), stomatal conductance ( g s ), mesophyllic conductance ( g m ) and electron-transport rate ( J cf ), and investigated their sensitivity to drought and temperature stress in sunlit and shaded leaves of four Mediterranean tree species ( Quercus ilex L., Pinus halepensis Mill., Arbutus unedo L. and Quercus pubescens Willd. ). Sunlit leaves, but not shaded leaves, showed a pronounced seasonality in the temperature responses of A net, g s, g m and J cf . All four species and variables showed a remarkably dynamic and consistent acclimation of the thermal optimum ( T opt ), reaching peaks in summer ~29–32 °C. Changes in the shape of the response curves were, however, highly species-specific. Under severe drought, T opt of all variables were on average 22–29% lower. This was accompanied by narrower response curves above all in P. halepensis, reducing the optimal range for photosynthesis to the cooler morning or evening periods. Wider temperature-response curves and less strict stomatal control under severe drought were accompanied by wilting and drought-induced leaf shedding in Q. ilex and Q. pubescens and by additional branch dieback in A. unedo . Mild winter conditions led to a high T opt (~19.1–22.2 °C), benefitting the evergreen species, especially P. halepensis . Seasonal acclimation of A net was explained better by g s and g m being less pronounced in J cf . Drought was thus a key factor, in addition to growth temperature, to explain seasonal acclimation of photosynthesis. Severe drought periods may exceed more frequently the high acclimatory capacity of Mediterranean trees to high ambient temperatures, which could lead to reduced growth, increased leaf shedding and, for some species such as A. unedo, increased mortality risk.